Personality Trait Changes After Device-Aided Therapy: Insights From Parkinson’s Patients and Their Close Relatives - Monica Scharfenort; Veronica Hernström; Kristina Rosqvist; Hanna Ljung; Maria H. Nilsson; Per Odin (Parkinson's Disease)
Conclusions: This study suggests perceived personality changes following DAT (DBS or LCIG), which vary by therapy and respondent role. Larger studies are needed, but the findings signal the importance of considering both patients’ and their relatives’ perspectives when assessing personality changes.